2006
DOI: 10.1194/jlr.m500564-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid cascade and epithelial barrier function during Caco-2 cell differentiation

Abstract: The small intestinal epithelium is a highly dynamic system continuously renewed by a process involving cell proliferation and differentiation. The intestinal epithelium constitutes a permeability barrier regulating the vectorial transport of ions, water, and solutes. Morphological changes during cell differentiation, as well as changes in the activity of brush-border enzymes and the expression of transport proteins, are well established. However, little is known about the arachidonic acid (AA) cascade underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 49 publications
5
55
0
Order By: Relevance
“…2). Thus, we observed that intestinal epithelial differentiation induces a decrease in both iPLA 2 activity and COX-2 expression and, consequently, a decrease in AA release and PGE 2 synthesis in parallel with a reduction in paracellular permeability and consequently the development of a barrier function that can be disrupted by the exogenous addition of PGE 2 [21]. Recently, we observed that this modulation of the epithelial barrier function is mediated by the interaction with PGE 2 receptors EP 1 and EP 4 .…”
Section: Role Of Eicosanoids In the Control Of Intestinal Barrier Funmentioning
confidence: 90%
See 1 more Smart Citation
“…2). Thus, we observed that intestinal epithelial differentiation induces a decrease in both iPLA 2 activity and COX-2 expression and, consequently, a decrease in AA release and PGE 2 synthesis in parallel with a reduction in paracellular permeability and consequently the development of a barrier function that can be disrupted by the exogenous addition of PGE 2 [21]. Recently, we observed that this modulation of the epithelial barrier function is mediated by the interaction with PGE 2 receptors EP 1 and EP 4 .…”
Section: Role Of Eicosanoids In the Control Of Intestinal Barrier Funmentioning
confidence: 90%
“…These events could also be necessary for the completion of epithelial cell differentiation, or at least for the development of the epithelial barrier function that is characteristic of differentiated epithelium [21]. Defining the molecular mechanisms of action of PGs on cell growth is an area of intense research.…”
Section: Role Of Eicosanoids In the Control Of Intestinal Epithelial mentioning
confidence: 99%
“…Caco-2 cells were kindly provided by Dr. David Thwaites at the School of Cell and Molecular Biosciences, University of Newcastle-upon-Tyne (United Kingdom), and were cultured as previously described (30). The cells (passages 107-121) were routinely grown in plastic flasks at a density of 5 ϫ 10 4 cells/cm 2 and cultured in DMEM containing 4.5 g/l D-glucose and 2 mM L-glutamine, supplemented with 1% (vol/vol) nonessential amino acids, 10% (vol/vol) heat-inactivated FBS, 100 U/ml penicillin, and 100 g/ml streptomycin at 37°C in a modified atmosphere of 5% CO 2 in air.…”
Section: Methodsmentioning
confidence: 99%
“…The medium was replaced every 3 days and on the day before the experiment. Experiments were performed in cultures 19 -21 days after seeding when cells are differentiated (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation